Association of socio-demographic factors on attitudes of nurses toward caring for older adults at Teaching Hospital Jaffna - Hazeem, A.M.; Mathusnka, M.K.I.; Kamalarupan, L.; Thanujanan, K. (Faculty of Allied Health Sciences, University of Jaffna, Sri Lanka., 2025)
Population ageing is increasing globally; hence, it’s crucial to give more focus to caring for them. Nurses are one of the key players among the multidisciplinary team who work with older adult patients. A nurse’s attitude towards the elderly affects their compassionate care. Objectives: To assess the association of socio-demographic factors with the attitude of nurses toward caring for older adults at Teaching Hospital Jaffna. Methodology: This was a hospital-based descriptive, cross-sectional study, conducted among 216 nurses working in Teaching Hospital Jaffna from May 2023 to August 2024. Ethical clearance was obtained from the Ethics Review Committee of the Faculty of Medicine, University of Jaffna. Data collection was done by a simple random sampling technique. A pre-designed and validated self-administered questionnaire was used to collect the data. SPSS 25 software was used to analyze the data. Univariate analysis was used to assess the attitude of nurses, and a Chi-Squared test was performed to identify the association of socio-demographic factors. Results: The response rate was 93.1%. The age range was 25 to 57 years old. The majority of them were female (70.4%). Nearly half were Sri Lankan Tamil (52.8%) and Hindus (47.7%). The majority were in medical wards (18.1%). Nearly more than half were below 05 years of working experience (63.9%). More than three-quarters were diploma holders (78.2%). The majority had a positive attitude (90.3%) based on considering 50% as the pre-determined cut-off value. A statistically significant relationship was found between attitude and currently working ward/unit (p=0.033) and higher education qualification (p=0.011). Conclusion: The Majority of the nurses had a positive attitude towards caring for older adults. Relevant wards and units take appropriate measures to ensure that nurses have the appropriate attitude toward caring for older adults.
Keywords: Attitude; Teaching Hospital Jaffna; Older adults; Nurses; Socio-demographic factors